Who dropped out? An approach to the reasons why higher education students abandoned a socio-educational program to support their educational paths - Mayer, Lilliana (2018)
Higher education massification process implies, by definition, an increase in enrollment rates. Furthermore, it brings new situations in terms of the social composition of the student body. In the intent of giving responses to the new problematics that these changes suppose, there have been implemented –and still are- different initiatives, related to higher education inclusion. Though most of them are State initiatives, in a smaller amount, others came from NGOs. In the following article, we present part of the results of a socio- educational Program evaluation that supports higher educational paths for underprivileged students in Argentina. Specifically, for this article, we will analyze the reasons that beneficiaries of that program, drop out of it. The analysis is based on a qualitative methodology which consisted on 15 in depth interviews to scholars who quitted the Program, inquiring both who “decided” to drop out and those who were asked to do so by the Program authorities. This research shows current trends in educational paths, which combine periods of dropping out, with the promise of –many times already accomplished- going back to university. Also, the need to make compatible studies and work